Ayat-Ayat Pendidikan Tentang Tujuan Pendidikan - Munir, Miftakhul (INSTITUT AGAMA ISLAM TARBIYATUT THOLABAH LAMONGAN, INDONESIA, 2020)
The purpose of education in Islam is inductively by looking at the arguments of naqli that already exist in the Koran and al-Hadith, also integrating them in the context of the needs of society in general in education, so that it is hoped that the objectives of education in Islam can be applied to discourse and reality. present. that some people think that worship is limited to performing prayers, fasting during the month of Ramadan, issuing zakat, performing Hajj, and saying shahada. But actually worship includes all the deeds, thoughts, and feelings that are confronted or relied on by Allah. The aspect of worship is the obligation of Muslims to study it so that they can practice it in the right way. Improving the quality of education so far has not shown satisfactory results. The low quality of education is caused by many things, including the inadequate quality and distribution of teachers, the lack of educational facilities and infrastructure, inappropriate curricula, the learning environment in schools and within the family and community is not yet supportive.